Serum Vitamin D Status in Newly Diagnosed Hypothyroid Patients (Bangladesh Journal of Nuclear Medicine, 2019)
More than billion people worldwide are vitamin D deficient. It is recognized to have function in bone and muscle development by regulating calcium and phosphorus metabolism. Its role as an immune modulator has recently been discovered. Deficiency of vitamin D has been discovered to be associated with various cardiovascular, infectious, malignant, hypothyroidism and autoimmune thyroid diseases. Prevalence of hypothyroidism and hypovitaminosis D in Bangladesh is not known but supposed to be high because our neighbor country India has high prevalence. Vitamin D mediates its effect through binding to vitamin D receptor (VDR) and activation of VDR- responsive genes. VDR gene polymorphism was found to be associated with autoimmune thyroid diseases. On the other way hypothyroidism either decreases the metabolism of vitamin D or prevents to activate it. A total of 38 adult hypothyroid otherwise healthy patients and age, sex, BMI, socioeconomic status matched euthyroid adults were included in the study. The mean age in the hypothyroid group was 37.82 ± 7.95 years and in the euthyroid group was 34.84 ± 8.61 years. Male participants were14 and female participants were 24 in each group. The mean value of serum vitamin D of healthy group was 17.11 ± 5.62 ng/ml  and in hypothyroid patients was 13.16 ± 4.29 ng/ml., Hypothyroid patients had significantly lower levels of serum Vitamin D3 as compared to controls (p =0.037,